Pyogenic Sacroiliac Arthritis: A Case Report - Boonma, Paithoon; Jerapralungsub, Somsak (The Bangkok Medical Journal, 2017)
Pyogenic sacroiliac arthritis is a rare entity. The most common bacterial organismis Staphylococcus aureus. More than 50% of cases have underlying diseases, for instance,trauma, immune deficiency, psoriasis, rheumatoid arthritis, post acupuncture and pelvicinflammation etc. In healthy persons, the arthritis is connected to sport medicine, overexercise, bike riding, and running and so on. Mild and nonspecific symptoms fever,lower back pain, gluteal or hip pain are presented. Radiographic image, computetomography (CT) and/or magnetic resonance image (MRI) with gadolinium (Gd) studyare recommended. Adequate and appropriate antibiotics are the initial treatment. Surgicalneedle aspiration and drainage is essential in case of no response to antibiotics, and isrecommended in chronic form debridement and arthrodesis.